Psychometric properties and minimal important differences of SF-36 in Idiopathic Pulmonary Fibrosis - Witt, Sabine; Krauss, Ekaterina; Barbero, María Asunción Nieto; Müller, Veronika; Bonniaud, Philippe; Vancheri, Carlo; Wells, Athol U; Vasakova, Martina; Pesci, Alberto; Klepetko, Walter; Seeger, Werner; Crestani, Bruno; et al. (Respiratory research, 2019)
BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is a rare disease with a median survival of 3-5 years after diagnosis with limited treatment options. The aim of this study is to assess the psychometric characteristics of the Short Form 36 Health Status Questionnaire (SF-36) in IPF and to provide disease specific minimally important differences (MID). METHODS: Data source was the European IPF Registry (eurIPFreg). The psychometric properties of the SF-36 version 2 were evaluated based on objective clinical measures as well as subjective perception. We analysed acceptance, feasibility, discrimination ability, construct and criterion validity, responsiveness and test-retest-reliability. MIDs were estimated via distribution and anchor-based approaches. RESULTS: The study population included 258 individuals (73.3% male; mean age 67.3 years, SD 10.7). Of them 75.2% (194 individuals) had no missing item. The distribution of several items was skewed, although floor effect was acceptable. Physical component score (PCS) correlated significantly and moderately with several anchors, whereas the correlations of mental component score (MCS) and anchors were only small. The tests showed mainly significant lower HRQL in individuals with long-term oxygen therapy. Analyses in stable individuals did not show significant changes of HRQL except for one dimension and anchor. Individuals with relevant changes of the health status based on the anchors had significant changes in all SF-36 dimensions and summary scales except for the dimension PAIN. PCS and MCS had mean MIDs of five and six, respectively. Mean MIDs of the dimensions ranged from seven to 21. CONCLUSION: It seems that the SF-36 is a valid instrument to measure HRQL in IPF and so can be used in RCTs or individual monitoring of disease. Nevertheless, the additional evaluation of longitudinal aspects and MIDs can be recommended to further analyse these factors. Our findings have a great potential impact on the evaluation of IPF patients. TRIAL REGISTRATION: The eurIPFreg and eurIPFbank are listed in https://clinicaltrials.gov ( NCT02951416 ).
Keywords: Surveys and Questionnaires; zdravotní stav; Humans; Longitudinal Studies; lidé středního věku; následné studie; Female; Aged; senioři; lidé; reprodukovatelnost výsledků; průzkumy a dotazníky; Patient-reported outcome; Rare diseases; Idiopathic Pulmonary Fibrosis; ženské pohlaví; longitudinální studie; Health Status; Male; Reproducibility of Results; Middle Aged; Psychometrics; Cross-Sectional Studies; Quality of life; mužské pohlaví; psychometrie; Idiopathic pulmonary fibrosis; průřezové studie; idiopatická plicní fibróza; Follow-Up Studies